Paleovegetasi Berdasarkan Bukti Palinologi Kala Pliosen Cekungan Banyumas - Kartika Anggi Hapsari; Sukarsa Sukarsa (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
Taxonomy is a branch of biology which is supported by palynological evidence. Palynology concerns to pollen and spore. The purposes of this research were to figure out plant diversity of Pliocene based on fossil pollens and to reconstruct vegetation and climates of Pliocene based on plant diversity. A survey has been conducted in Bungkanel, Purbalingga. Sampling was done for 25 sediment samples and then they were crushed, carbonate-, sulfide-, fluoride-, and organic-separated, centrifuged, oxidizing, alkali water-bathed, and mounted. Pollen and spore were identified in the laboratory with a binocular microscope. Data were analyzed descriptively, clustering, biostratigraphic Ranging-Zone, AP-NAP-Spore and PMI analysis has been done to determine the taxon, sediment age, paleo-diversity, paleo-vegetation and paleo-climate. The result showed that there were sixteen genera and three species of terrestrial palynomorph; two phyla, one class and one order of marine palynomorph. The Age of Pliocene was indicated by the appearance of Podocarpus imbricatus and Stenochlaena laurifolia (Stenochlaenidites papuanus).  The results of clustering analysis showed that there were six groups of samples with Shannon-Wienner H’ diversity index of <2. However, the palinological diagram showed that there were three local zones of vegetation-alteration. In addition, AP/NAP/Spores and PMI indicated that there were six zones of climate change.